Branding Agama dalam Membentuk Identitas Politik: Kajian Mengenai Selebriti Islam pada Aksi 212 - Revta Fariszy; Vegasari Adya (Universitas Gadjah Mada, 2020)
The 212 Rally has many other interest outside the religious context. The rally strengthens the identity of Muslims and indicating that the hegemony of religious is able to contribute to the world of politics. Unlike usual, 212 Rally presents actors whose are not only from politicians or religious circles, but also public figures from the entertainment industry. However, the participation of public figures is full of political interests, because some of them are incorporated with certain political parties. This paper analyzes the construction of the religious identity of public figures and their relation to politics. Referring to the theory and concept of political identity and personal branding, there are indications that public figures construct their religious identity for political purposes and agendas.PrabowoSubiantodanCalonWakilPresidenSandiaga Uno dalam Pilpres 2019 (Afriyan, 2018).Takhanyaitu,RizieqShihabsebagaiImamBesarFPIpuntelahmenyatakandukungannyapadakubucalonpresidenPrabowoSubiantodanmenyerukankepadapesertaAksi212untukmengiku alurdukungannya(Siddiq,2018).Secaradaklangsung,aksiinimenjadipembukaaliransuaraPilprestahun2019.SelainsinggungandenganPilpres2019,Aksi212inijugamengandungbahasantentangidentas.Identasyangdirepresentasikanpadaaksii